Pemanfaatan Limbah Kelapa Muda Di Desa Pematang Johar - Ardhansyah Putra; Dwi Saraswati (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
The purpose of this activity is to help partners solve problems in facing the new normal so that partners, especially mothers, can create innovative business opportunities in the form of processing young coconut chips and utilizing young coconut waste into economic value in the form of plant polybags.The priority problems faced by natural partners include partners who do not have the knowledge and skills in processing young coconut meat / by turning into young coconut chips which are more valuable for sale and do not yet have the skills and innovations in utilizing young coconut waste into polybags for ornamental plants and do not yet have the knowledge to promote and market the processed products of young coconut chips and plant polybags from young coconut waste.The benefits of this activity are expected to create new business opportunities and foster an independent entrepreneurial spirit for PKK mothers so that they can improve skills and income. The implementation method is education and counseling, conducting focus group discussions, training and production assistance, website design and promotion and online marketing.